Voltage stability analysis of wind power plant integration into transmission network of Nepal - Dharel, Sagar; Maharjan, Rabindra (Journal of Engineering Issues and Solutions, 2021)
Government of Nepal has realized that wind energy could become a major source of alternative energy to solve energy crisis in the country as well as serve the purpose of energy mix. Various studies have identified several locations with potential for wind power generation in Nepal. The integration of wind power plant to the national grid, however, raises concerns regarding the power system stability. The voltage stability of the grid is a key issue, the effect on which increases with the increase in wind power penetration in the grid. This study performs voltage stability analysis due to high penetration of wind power in Integrated Nepalese Power System (INPS). Both steady state and dynamic stability study is performed using the power system simulation software DigSILENT/PowerFactory for different types of wind turbine generators.